Hubungan Dukungan Keluarga Dengan Kepatuhan Ibu Hamil Dalam Mengonsumsi Tablet Fe - Srifitayani, Nur Rahma; Hartati, Andi; Rahmat, Rezqiqah Aulia (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Anemia during pregnancy is one of the most common health problems and increases the risk of complications such as bleeding, premature birth, and low birth weight. The primary preventive measure recommended by the Ministry of Health is the consumption of at least 90 iron tablets during pregnancy. However, compliance with iron supplements by pregnant women remains low. One important factor influencing this compliance is family support. This study aims to analyze the relationship between family support and adherence by pregnant women in taking iron tablets. The study used a cross-sectional design with a sample of 120 pregnant women selected using purposive sampling in the working area of ​​Community Health Center X. The instruments used included a family support questionnaire and an adherence questionnaire regarding iron tablet consumption. Data were analyzed using the chi-square test. The results showed that the majority of pregnant women (65.8%) had good family support, and 63.3% were compliant with iron tablet consumption. There was a significant relationship between family support and adherence by pregnant women in taking iron tablets (p-value = 0.001). In conclusion, family support plays a significant role in improving adherence by pregnant women in taking iron tablets. Therefore, health interventions must involve families to increase the success of anemia prevention programs.